Analysis of The Implementation of The Management Planning, Organizing, Actuating, Controlling in BES PPJA (Case Study of The Santri Executive Board of The Jagad ‘Alimussirry) (Journal Intellectual Sufism Research (JISR), 2023)
This research aims to analyze the application of the management functions Planning, Organizing, Actuating and Controlling at BES PPJA Pondok Pesantren Jagad 'Alimussirry. This research is a descriptive qualitative type and was conducted using interviews, observation and documentation. The results of the research show that the Executive Board of the Jagad 'Alimussirry Student Islamic Boarding School has implemented the POAC management function well. Activities in planning include establishing regulations, electing the BES PPJA president, work programs, and establishing AD/ART. Organizing involves the process of dividing tasks and job desks as well as the BES PPJA structure. The actuating function includes the realization of work programs in a ministry. Meanwhile, the controlling function includes direct supervision of the PSDM director by evaluating each work program. This shows that the implementation of planning, organizing, actuating, and controlling in the Executive Board of the Santri Islamic Boarding School Jagad 'Alimussirry can help improve the quality of the organization. Thus, it can be concluded that the management of the BES PPJA Executive Board for Santri Pondok Pesantren Jagad 'Alimussirry has implemented the POAC management function well. So that in its implementation it can improve the quality and productivity of the Jagad 'Alimussirry Islamic Boarding School Santri Executive Board.